Systematic Characterization of bZIP Transcription Factors Required for Development and Aflatoxin Generation by High-Throughput Gene Knockout in Aspergillus flavus - Qianqian Zhao; Hao Pei; Xiaoling Zhou; Kai Zhao; Min Yu; Guomin Han; Jun Fan; Fang Tao (Journal of Fungi, 2022)
The basic leucine zipper (bZIP) is an important transcription factor required for fungal development, nutrient utilization, biosynthesis of secondary metabolites, and defense against various stresses. Aspergillus flavus is a major producer of aflatoxin and an opportunistic fungus on a wide range of hosts. However, little is known about the role of most bZIP genes in A. flavus. In this study, we developed a high-throughput gene knockout method based on an Agrobacterium-mediated transformation system. Gene knockout construction by yeast recombinational cloning and screening of the null mutants by double fluorescence provides an efficient way to construct gene-deleted mutants for this multinucleate fungus. We deleted 15 bZIP genes in A. flavus. Twelve of these genes were identified and characterized in this strain for the first time. The phenotypic analysis of these mutants showed that the 15 bZIP genes play a diverse role in mycelial growth (eight genes), conidiation (13 genes), aflatoxin biosynthesis (10 genes), oxidative stress response (11 genes), cell wall stress (five genes), osmotic stress (three genes), acid and alkali stress (four genes), and virulence to kernels (nine genes). Impressively, all 15 genes were involved in the development of sclerotia, and the respective deletion mutants of five of them did not produce sclerotia. Moreover, MetR was involved in this biological process. In addition, HapX and MetR play important roles in the adaptation to excessive iron and sulfur metabolism, respectively. These studies provide comprehensive insights into the role of bZIP transcription factors in this aflatoxigenic fungus of global significance.